Identifying the Best Treatment in Adult Spinal Deformity: A Decision Analysis Approach. Issue 1 (April 2016) - Acaroglu, Emre; Yavuz, Aysun Çetinyürek; Güler, Ümit Özgür; Yuksel, Selcem; Yavus, Yasemin; Ayhan, Selim; Sabat, Montse Domingo; Pellise, Ferran; Perez-Grueso, Francisco Javier Sanchez; Alanay, Ahmet; Obeid, Ibrahim; Kleinstuck, Frank; et al.
Introduction: Adult spinal deformity (ASD) is a major public health problem. There are pros and cons of the available treatment alternatives (surgical or non-surgical) and it had been difficult to identify the best treatment modality. Aim of this study is to construct a statistical decision analysis (DA) model to identify the optimum overall treatment in ASD. Material and Methods: From an international multicentre database of ASD patients (968 pts), 535 who had completed 1 year follow-up (371 non-surgical –NS), 164 surgical –S), constitute the population of this study. DA was structured in two main steps of: 1) Baseline analysis (Assessing the probabilities of outcomes, Assessing the values of preference –utilities-, Combining information on probability and utility and assigning the quality adjusted life expectancy (QALE) for each treatment) and 2) Sensitivity analysis. Results: 432 patients (309 NS, 123 S) had baseline and 1 year follow-up ODI measurements. Overall, 104 (24.1%) were found to be improved (a decrease in ODI > 8 points), 225 (52.1%) unchanged (−8 > ODI > 8) and 65 deteriorated. Surgery presented with a higher chance of improvement (54.2%) versus NS (9.7%) (Table 1a). The overall QALE ranged from 56 to 69 (of 100 years) and demonstrated better final outcomes in the NS group, although this group had also started with higher QALE. There were improvements in overall QALE in both groups but this was significant only in the surgical group (Table 1b). In addition, in the subgroup of patients with significant baseline disability (ODI > 25) surgery appeared to yield marginally better final QALE (Table 1c). Conclusion: This study demonstrated that a single best treatment modality for ASD may not exist. Conservative treatment appears to yield higher (up to 6%) QALE compared with surgery, probably secondary to a higher baseline QALE; except in patients with significant disability at baseline. On the other hand, surgery provides a significantly higher increase in QALE and chances of improvement at 1st year are significantly lower with NS treatment.